Pediatric Heart Sounds - McConnell, Michael E. (Springer London : Imprint: Springer, 2008)
There is, even now, no other basic physical examination skill is more important than cardiac auscultation. When a patient presents with a soft systolic murmur on auscultation, only good physical examination skills will allow the examiner to reassure the patient that the murmur is non-pathologic. This book is not an exhaustive "encyclopedia" listing every possible abnormal sound with the appropriate clinical response. Instead, the goal is to increase the reader’s confidence using the stethoscope in an organized fashion, and once they have the organized system of auscultation, to improve their ability to tell pathologic from normal heart sounds.